Penggunaan Media Ular Tangga Tematik (ULGATIK) untuk Meningkatkan Hasil Belajar dan Aktivitas Siswa kelas IIA SDN 1 Landungsari - Ida Cholifah (Jurnal Bidang Pendidikan Dasar, 2021)
The learning outcomes of class IIA students were many below of KKM. When studying of the theme 6, only 3 students scored above the KKM and who have sufficient attention to thematic. The aims of this study were to improve student learning outcomes and activities by using the thematic snake and ladder media. The results in the first cycle, score PPKN 76%, score Indonesian 70%, score mathematics 53%, score PJOK 72%, SBDP 62%. The students’ activities of Cycle were consisting of listening to the teacher's explanation 42%, playing snakes and ladders 59%, answering questions 45%. In the second cycle, PPKN 86%, the Indonesian language 83%, math 89%, PJOK 82%, SBDP 84%. In the Cycle II consisted of listening to the teacher's explanation 77%, playing snakes and ladders 93%, answering questions 78%. To sum up, the use of the thematic snake and ladder media can improve student learning outcomes and activities